2020
DOI: 10.3892/ijmm.2020.4587
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol myristate acetate induces cellular senescence in rat microglia in vitro

Abstract: The present study aimed to establish a cellular model to test the hypothesis that oncogene-induced senescence (OIS) is triggered by aging-related activation of microglia. Primary microglia were incubated with phorbol 12-myristate 13-acetate (PMA), and β-galactosidase (β-Gal) staining was applied to subsequent assessment of cellular senescence. Moreover, flow cytometry was employed for examinations of cell cycle arrest and senescence-associated proteins, p53 and p21 were measured by western blotting. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Thus, it is possible that part of the β-galactosidase in senescent cells could end up on the cell surface. This is at least consistent with our findings that: (i) PMA and LPS induce β-galactosidase release [as both PMA and LPS are reported to induce microglial senescence (Yu et al, 2012;Cao et al, 2020)], and (ii) microglia in the brains of aged mice appear to have βgalactosidase on their cell surface. Note, however, that we do not know whether PMA or LPS induced microglial senescence in our cultures, and much more work would be required to confirm that senescent microglia expose β-galactosidase.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, it is possible that part of the β-galactosidase in senescent cells could end up on the cell surface. This is at least consistent with our findings that: (i) PMA and LPS induce β-galactosidase release [as both PMA and LPS are reported to induce microglial senescence (Yu et al, 2012;Cao et al, 2020)], and (ii) microglia in the brains of aged mice appear to have βgalactosidase on their cell surface. Note, however, that we do not know whether PMA or LPS induced microglial senescence in our cultures, and much more work would be required to confirm that senescent microglia expose β-galactosidase.…”
Section: Discussionsupporting
confidence: 92%
“…Phorbol 12-myristate 13-acetate (PMA) is a protein kinase C activator that has been reported to induce β-galactosidase and senescence of microglia (Cao et al, 2020). So, we tested whether PMA treatment of microglia could induce β-galactosidase release, and found that BV-2 microglia cultured with PMA had significantly more β-galactosidase activity on the cell surface (Figures 1C, D) and released significantly more β-galactosidase activity into the culture medium (Figures 1E, F).…”
Section: Activation Of Microglia Induces β-Galactosidase Releasementioning
confidence: 99%
“…Besides astrocytes, also senescent microglia might influence the pro-inflammatory state in the brain. Experiments performed on microglia derived from rat brain cultured in vitro indicated that those cells can undergo stress-induced senescence, which is accompanied by SASP (Cao et al, 2020). Moreover, it was demonstrated in the elegant studies performed by Sierra et al (2007) that microglia derived from old mice are characterized by higher granularity (flow cytometry analysis) and significantly increased expression of TNFα, IL-1β, IL-6.…”
Section: Neuroinflammation and Saspmentioning
confidence: 99%
“…Besides astrocytes, microglia can also become senescent and influence the pro-inflammatory state of the brain. For example, microglial cells derived from rat brain and cultured in vitro undergo stress-induced senescence, which is accompanied by the SASP [ 75 ]. Microglia of aged mice is characterized by higher granularity and increased expression of TNF-α, IL-1β, IL-6, cytokines that reflect development of the SASP [ 76 ].…”
Section: Molecular Regulation and Pathological Implications Of The Saspmentioning
confidence: 99%